Drug‐related deaths associated with vaping product use in the United Kingdom. (26th March 2021) - Roberts, Emmert; Copeland, Caroline; Robson, Deborah; McNeill, Ann
Abstract : Background and Aims: Between March 2019 and February 2020 there was an outbreak of acute lung injury associated with vaping tetrahydrocannabinol (THC), contaminated with vitamin E acetate, in the United States. To date, there has been no comprehensive study of drug‐related deaths associated with vaping products in the United Kingdom. We aimed to identify any trends in drug‐related deaths associated with vaping product use in the United Kingdom. Methods: We retrospectively identified any deaths associated with the use of vaping products reported to the UK National Programme on Substance Abuse Deaths (NPSAD). This contains voluntarily reported information from UK Coroners on more than 42 000 deaths related to psychoactive drugs, other than nicotine or caffeine, which occurred between 1997 and 2020. Results: Two drug‐related deaths were reported which were associated with vaping products, one person having died in 2017 and one in 2018. Both decedents were men currently serving prison sentences in England and were aged 26 and 42 years at the time of death. Both deaths were associated with recent use of Synthetic Cannabinoid Receptor Agonists (SCRAs), with no other substances found to be implicated in death. No details regarding the type of vaping products were available. Conclusions: In a UK sample (1997 to 2020) of 42 000 deaths related to psychoactive drugs other than nicotine or caffeine, only two deaths were associated with vaping products, and those involved use of synthetic cannabinoid receptor agonists.